Is the Middle East and North Africa Region Achieving Its Trade Potential? - Soderling, Ludvig (IMF Working Papers; Working Paper ;, 2005)
This paper analyzes export performance in the Middle East and North Africa (MENA) using a gravity model applied to panel data. It addresses two questions: (i) are there significant unexploited export markets for the MENA region?; and (ii) have integration efforts with the EU since the mid-1990s yielded positive results? The results suggest that several MENA countries are substantially underexploiting the United States as an export market. Moreover, the impact of integration efforts with the European Union has been moderate overall but significant in individual cases.